2004
DOI: 10.1044/1092-4388(2004/058)
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Loudness Manipulations in Dysarthria

Abstract: Both rate reduction and increased loudness reportedly are associated with an increase in the size of the articulatory-acoustic working space and improved acoustic distinctiveness for speakers with dysarthria. Improved intelligibility also has been reported. Few studies have directly compared rate and loudness effects for speakers with dysarthria, however, although rate reduction and increasing vocal loudness are common treatment techniques. In the current study, 15 speakers with dysarthria secondary to multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
266
12
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(319 citation statements)
references
References 39 publications
29
266
12
12
Order By: Relevance
“…Some studies have also reported reduced sound pressure levels (SPLs; Fox & Ramig, 1997;Skodda, Visser, & Schlegel, 2011b;Tjaden et al, 2013;Walsh & Smith, 2011). However, other studies have reported no differences in mean SPL for speakers with PD relative to healthy controls (Canter, 1963;Sadagopan & Huber, 2007;Tjaden & Wilding, 2004). Last, a variety of studies have reported rate abnormalities in PD (Canter, 1963(Canter, , 1965Flint et al, 1992;Hammen & Yorkston, 1996;Ludlow & Bassich, 1983;Metter & Hanson, 1986;Solomon & Hixon, 1993;Skodda & Schlegel, 2008), although other studies reported no differences in rate relative to healthy controls (Ackermann & Ziegler, 1991;Caligiuri, 1989;Goberman et al, 2002).…”
Section: Acoustic Characteristics Of Pdmentioning
confidence: 97%
See 3 more Smart Citations
“…Some studies have also reported reduced sound pressure levels (SPLs; Fox & Ramig, 1997;Skodda, Visser, & Schlegel, 2011b;Tjaden et al, 2013;Walsh & Smith, 2011). However, other studies have reported no differences in mean SPL for speakers with PD relative to healthy controls (Canter, 1963;Sadagopan & Huber, 2007;Tjaden & Wilding, 2004). Last, a variety of studies have reported rate abnormalities in PD (Canter, 1963(Canter, , 1965Flint et al, 1992;Hammen & Yorkston, 1996;Ludlow & Bassich, 1983;Metter & Hanson, 1986;Solomon & Hixon, 1993;Skodda & Schlegel, 2008), although other studies reported no differences in rate relative to healthy controls (Ackermann & Ziegler, 1991;Caligiuri, 1989;Goberman et al, 2002).…”
Section: Acoustic Characteristics Of Pdmentioning
confidence: 97%
“…Acoustic variables likely explaining these intelligibility variations are suggested in a variety of studies. For example, segmental metrics such as static and dynamic vowel measures, consonant spectral moments, and consonant distinctiveness measures have been reported as predictors of intelligibility (Amano-Kusumoto, Holsom, Kain, & Aronoff, 2014;Fogerty, 2013;Fogerty & Humes, 2010;Kay, 2012;Kim et al, 2011;Lansford & Liss, 2014;Maniwa, Jongman, & Wade, 2008;Owren & Cardillo, 2006;Tjaden & Wilding, 2004;Turner et al, 1995;Weismer, Martin, Kent, & Kent, 1992). In addition, suprasegmental measures of F0 and global timing measures have shown to be strong predictors of intelligibility (Bradlow, Torretta, & Pisoni, 1996;Bunton, Kent, Kent, & Duffy, 2001;Kim et al, 2011;Laures & Weismer, 1999).…”
Section: Clear Speech Instructionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first author heard the speech stimuli multiple times to ensure that the chosen monologue samples were representative of the speaker's natural speech pattern. The selected speech stimuli were edited to be of approximately 2 s each in Audacity software (version 2.0.5), and each utterance consisted of one to two complete sentences, similar to previous studies (Nagle & Eadie, 2012;Spielman, Ramig, Mahler, Halpern, & Gavin, 2007;Tjaden & Wilding, 2004;Weismer & Laures, 2002). All stimuli were amplitude normalized, and speech-shaped noise was added for judgments of intelligibility.…”
Section: Speech Stimulimentioning
confidence: 99%